Cognition and addiction . Issue 3 (30th September 2019) - Verdejo-Garcia, Antonio; Garcia-Fernandez, Gloria; Dom, Geert
Abstract : In this targeted review, we summarize current knowledge on substance-use disorder (SUD)-related cognitive deficits, the link between these deficits and clinical outcomes, and the cognitive training, remediation, and pharmacological approaches that have the potential to rescue cognition. We conclude that: (i) people with SUDs have moderate deficits in memory, attention, executive functions, and decision-making (including reward expectancy, valuation, and learning); (ii) deficits in higher-order executive functions and decision-making are significant predictors of relapse; (iii) cognitive training programs targeting reward-related appetitive biases, cognitive remediation strategies targeting goal-based decision-making, and pharmacotherapies targeting memory, attention, and impulsivity have potential to rescue SUD-related cognitive deficits. We suggest avenues for future research, including developing brief, clinically oriented harmonized cognitive testing suites to improve individualized prediction of treatment outcomes; computational modeling that can achieve deep phenotyping of cognitive subtypes likely to respond to different interventions; and phenotype-targeted cognitive, pharmacological, and combined interventions. We conclude with a tentative model of neuroscience-informed precision medicine.